Pediatric cervical spine fracture case report: Best practice to delay transition to rear-facing restraint. (August 2021) - Stolworthy, Christopher; Hu, Jonathan; Merritt, Neil
Abstract: Pediatric physicians and motor vehicle safety experts have been advocating for change in child passenger restraint practices for decades. As professional recommendations evolve to support extended rear-facing restraint, actual practices remain disparate. We report a case of pediatric cervical spine fracture due to motor vehicle collision, an uncommon, yet predictable, pattern of injury for which prevention education is undoubtedly preferable to managing the consequences of premature forward-facing in vulnerable pediatric patients. Currently, 9 kg is a minimum legal standard for forward-facing child restraint system use in Ontario, rather than a recommended transition time. We advise that parents should be counselled on the benefits of rear-facing as long as possible and discuss realistic transition times using their child restraint system manual as a reference, with the goal of approaching, but not exceeding, the maximum weight, height and fit requirements for optimal safety. Highlights: A case of pediatric cervical spine fracture due to a motor vehicle collision Prevention education is crucial to reduce risk of pediatric cervical spine injury. 9 kg is a minimum legal standard for FFCRS rather than recommended transition time. Counsel parents on benefits of extended rear-facing and realistic transition times Aim to approach but not exceed maximum requirements of child restraint systems